2000
DOI: 10.1177/014920630002600409
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy-Performance Spirals: An Empirical Test

Abstract: This study examined the pattern of the relationships between self-efficacy and performance in an experiment involving 148 students who worked on a manufacturing task over four trials. Task feedback and task experience, two variables that may influence the occurrence of efficacy-performance spirals, were also investigated. Results indicated strong support for a significant relationship between self-efficacy and performance over time. However, the pattern of changes in self-efficacy and performance from trial-to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
74
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(81 citation statements)
references
References 26 publications
7
74
0
Order By: Relevance
“…The results of this study are also consistent with those that Parker et al (2006), Parker and Collins (2010), Locke and Latham (1990), and Shea and Howell (2000) obtained. Their results showed that job performance had a significant and positive correlation with self-efficacy.…”
Section: Discussionsupporting
confidence: 93%
“…The results of this study are also consistent with those that Parker et al (2006), Parker and Collins (2010), Locke and Latham (1990), and Shea and Howell (2000) obtained. Their results showed that job performance had a significant and positive correlation with self-efficacy.…”
Section: Discussionsupporting
confidence: 93%
“…In control theory (Carver & Scheier, 2001;Powers, 1973), the discrepancy reduction tendency is emphasized, meaning that individuals regulate their invested effort (e.g., proactive career behaviours) to maintain a desired state (e.g., a career goal, current career track). Consistent with this prediction, several past studies have shown on an intraindividual level that higher self-efficacy is associated with decreases in task effort (e.g., Vancouver, Thompson, Tischner, & Putka, 2002;Vancouver, Thompson, & Williams, 2001), resource allocation (Beck & Schmidt, 2015), and performance levels (Shea & Howell, 2000;Vancouver et al, 2002), whereas lower self-efficacy motivates increased effort, resource allocations, and performance. Consequently, people with higher levels of control may decrease their effort in working towards eliminating goal-state discrepancies, due to their anticipation of less needed resources to reach their goals.…”
mentioning
confidence: 57%
“…For example, Price and Allen (1990) suggested that processes of social norm change can be expected to take years to unfold. In contrast, a study of the mutually reinforcing relationships between perceived efficacy and performance assessed four trials in a period of 2 hours (Shea & Howell, 2000). Clearly, the longitudinal design must fit the phenomenon under study.…”
Section: A Reinforcing Spirals Approach To Understanding Media Use Anmentioning
confidence: 99%